Kesesuaian Media Tumbuh Stek Akar Sukun - Jumani Jumani; Heni Emawati (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
The results showed that the average growth of roots at the age of 4 months was very real different between treatments and the best growth was in medium roasted husk fuel (SB), husk fuel humus (SBH) and then burn the chaff sand (SBP) with the following average husk fuel the growth of root length 4.33 cm, 3.33 cm and 2.00 cm.Shoot growth showed that the average growth of shoots at the age of 4 months was very real different between treatments and the best growth medium roasted husks (SB), husk fuel humus (SBH) and husk sand burns (SBP) with the following average husk fuel shoot growth was 3.67 cm, 3.00 cm and 2 cm. Best growth in medium roasted husks due to aeration and water absorption media quite well when too wet and dries quickly when the watering less easily monitored and medium roasted husks too sterile of fungus and nest for easy root growth and subsequent shoot will also grow.